From Bullet to the Ballot: A Case Study of the East Timorâs Referendum as Viewed by Newspapers of Kompas and Republika in Jakarta - Nurjaman, Nurjaman; Suwirta, Andi; Kamsori, Moch Eryk (TAWARIKH, 2012)
ABSTRACT: The conflicts occured in East Timor, since it integrated with Indonesia in 1976, could be described as a conflict between Indonesian government and pro-independence group in one side; and in other side, a conflict between pro-integration and pro-independence groups. Meanwhile, such conflicts ended with referendum option in 1999, so that it could be described as conflict resolution through the mechanism of âfrom bullet to the ballotâ. This paper studied the policy of Indonesian governemnt, under the rule of President B.J. Habibie, giving special autonomy option or independence to East Timor as noted in two newspapersâ views in Jakarta, namely âKompasâ and âRepublikaâ. Such two newspapers had different ways in viewing every political events in East Timor. âKompasâ, which initially supported, then tried to keep at a distance to government and became critical to the government. It was different with âRepublikaâ which was still consistent to support every Indonesian government policy under the rule of President B.J. Habibie.KEY WORDS: Conflict and integration, Indonesian government, East Timor, referendum, and the mass media views.Â Â Â Â Â About the Authors: Nurjaman, S.Pd. is an Alumnus of History Education Department, Faculty of Social Studies Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40514, West Java, Indonesia. Andi Suwirta, M.Hum. and Moch Eryk Kamsori, S.Pd. are the Lecturers at the Department of History Education UPI. They can be contacted via e-mail at: zamenisme21@gmail.com dan atriwusidna@gmail.comHow to cite this article? Nurjaman, Andi Suwirta & Moch Eryk Kamsori. (2012). âFrom Bullet to the Ballot: A Case Study of the East Timorâs Referendum as Viewed by Newspapers of Kompas and Republika in Jakartaâ in TAWARIKH: International Journal for Historical Studies, Vol.4(1) October, pp.103-122. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 22, 2012); Revised (September 24, 2012); and Published (October 28, 2012).